Personnel innovations as a factor in increasing the competitiveness of the enterprise - Leshchynskyi, V.P. (Ways to Improve Construction Efficiency, 2021)
The article substantiates the provisions and practical recommendations for assessing the innovation of staff, human resource management systems in enterprises. The peculiarities of innovative staff development are determined and the degree of influence of human resources innovation on staff competitiveness is assessed. It is substantiated that competitiveness is one of the most important categories of market economy. Significant for the competitiveness of the enterprise together with technologies and methods of production organization are the availability of professional staff, level of motivation, working conditions and various factors that ensure the level of employee competitiveness. The necessity of personnel development as a factor in increasing the efficiency of the enterprise is substantiated. An analysis of existing approaches to determining the competitiveness of staff. The influence of modern global trends is noted. With the need for the transition of Ukraine's economy to a post-industrial model of development, its digitization and robotization, there is a need for new approaches to the formation of knowledge, skills, competencies of personnel. In particular, in the use of the competency approach, which is directly related to changes in the nature and content of work, as well as changes in education and training. Conditions must be created for the integration of education and training in accordance with the needs of the labor market, as well as for ensuring the mobility of staff in several dimensions: vertical (career development), horizontal (industry change) and spatial (territorial relocation). The main advantages of the competency approach are integration potential and flexibility. The key characteristics and features of human resources management as a factor in supporting the growth of innovative development of the enterprise are summarized.